Pseudocyst-Portal Vein Fistula with Hepatic Pseudocysts as Life-Threatening Complication of Pancreatitis: A Case Series with Review of Literature - Pritam Das; Dhruv Thakur; Gourav Jyoti Borah; Naganath Kashinath Wodeyar; Kartik Balankhe; S. Rakesh Kumar; Samir Mohindra (Journal of Digestive Endoscopy, 2024)
Pseudocyst-portal vein fistula (PPVF) manifesting as hepatic pseudocyst is a very rare vascular complication of pancreatitis. We present three cases of pancreatitis manifesting as PPVF with hepatic pseudocyst. One of them had a symptomatic pseudocyst with nonpatent portal vein with sepsis, which was managed with endoscopic drainage. The second case had a symptomatic pseudocyst with nonpatent portal vein without any manifestation of sepsis or gastrointestinal (GI) bleed, which was managed conservatively with gradual improvement. The third case manifested with sepsis with organ failure and GI bleed; portal vein reconstruction was planned, but the patient succumbed to sepsis. During a follow-up of 12 months, the first two patients had an uncomplicated course. Patency of the portal vein played a key role in determining the further course of treatment. In case of a nonpatent portal vein, endoscopic drainage may be preferred in case of symptomatic patients, whereas asymptomatic patients may be managed conservatively.